??The Relative Importance of Predators for the Control of Nephotettix Spp. on Rice ? - AHAD, M.A.; SHAHJAHAN, M.; TALUKDER, F.A. (Biological Sciences - PJSIR, 1995)
The rice green leafhoppers, Nephotettix spp. (Homoptera: Cicadellidae is one of the most devastating pests of rice throughout the rice growing areas of Asia [1-4]. They act as an efficient vector of rice tungro virus, one of the most menacing disease of rice [1].